2018
DOI: 10.5296/gjes.v4i1.12224
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using Blogs to Enhance the Writing Skill of English Language Learners at a Saudi University

Abstract: The purpose of this paper is to investigate the use of web blogs as a supplementary tool for teaching English. It focuses on studying the effectiveness of using blog exchanges for enhancing the Saudi female university students' English writing, especially the vocabulary usage. The participants of the current study were thirty-seven Saudi female preparatory year students from the English Language Institute (ELI) at King Abdulaziz University (KAU). Their ages ranged between 18 to 20 years of age. All participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 9 publications
1
25
1
Order By: Relevance
“…The research results and discussion show several similarities to the results of previous studies in that the use of Blog media in Writing teaching learning process can improve the students' writing scores, can increase the students' motivation and enthusiasm, and leads a positive attitude toward the use of digital technology in the classroom. Meanwhile, compared to the results of previous studies Chawinga (2017) Alsubaie & Madini (2018) Kohsamut & Sucaromana (2017) Said et al, (2013), several differences also can be found. Because this research also used Slide media in control group, and integrated reasoning level in measuring the students' writing ability, it can be seen that different media will also have different effect to the students' with different reasoning level.…”
Section: Difference In the Ability To Write An English-language Research Proposal Between Groups Of Students Given Blog Media And Those Gcontrasting
confidence: 48%
See 1 more Smart Citation
“…The research results and discussion show several similarities to the results of previous studies in that the use of Blog media in Writing teaching learning process can improve the students' writing scores, can increase the students' motivation and enthusiasm, and leads a positive attitude toward the use of digital technology in the classroom. Meanwhile, compared to the results of previous studies Chawinga (2017) Alsubaie & Madini (2018) Kohsamut & Sucaromana (2017) Said et al, (2013), several differences also can be found. Because this research also used Slide media in control group, and integrated reasoning level in measuring the students' writing ability, it can be seen that different media will also have different effect to the students' with different reasoning level.…”
Section: Difference In the Ability To Write An English-language Research Proposal Between Groups Of Students Given Blog Media And Those Gcontrasting
confidence: 48%
“…Wheeler in Chawinga states that social media such as Twitter and Blog can be combined to make it easier for both students and lecturers to participate and communicate actively in educational activities. Alsubaie & Madini (2018) declared that an improvement in the students' writing performance after using the blog entries. In addition, the research experiment contributed to the extension of their vocabulary knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Then, for qualitative data, the writer used purposeful sampling (purposive sampling). The researcher selected 6 of 13 samples based on the strategies and phases [11].…”
Section: Methodsmentioning
confidence: 99%
“…Blogs are thought to be one of the widely used web tools in learning English language skills. Alsubaie and Madini (2018) stated that learners would be able to ensure self-learning when they will write up in the blog or in the web page. The problem-solving activities energize them, and they open the problem box by solving the blog matters with peer interaction and motivation.…”
Section: Blogging For Interaction and Motivationmentioning
confidence: 99%